PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN JASA TRANSPORTASI OJEK ONLINE (STUDI PADA KONSUMEN GOJEK DI TASIKMALAYA) - Eline Nuha Nurrohmah Gika; Rani Dhever Hani; Daffina Amalia Az Zahra; Auliya Nur Kholishah; Syti Sarah Maesaroh (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
In the times that are increasingly moving forward, there are many inventions, tools, and facilities that can be implemented by a company in marketing or attracting consumer interest. In this case, humans are required to always keep up with the changing conditions that continue to develop so that there is a change in consumer behavior to become completely digital, one of which is using online transportation and inter-culinary services. Service quality and price are two things that significantly affect customer satisfaction so that the company can attract customers to use the services that have been provided. The aim of the study was to identify the effect of service quality and price on customer satisfaction with GOJEK online motorcycle taxi transportation services. This research method uses a quantitative approach with descriptive analysis. The sampling technique used a nonprobability sampling technique with an accidental sampling approach with 34 respondents using a Likert scale. Research respondents are Gojek application users who live in Tasikmalaya. This research instrument has met the criteria of validity and reliability. Data processing uses SPSS software version 26 and uses multiple linear regression for data analysis. This study uses the Multiple Linear Regression Analysis method. Based on the research results, it is known that the service quality variable (X1) has a partially significant effect on the dependent variable, namely customer satisfaction (Y). The price variable (X2) has a partially significant effect on the dependent variable, namely customer satisfaction (Y) and the price variable (X2) has a more dominant influence.Keywords: price; service quality; customer satisfaction.